2014
DOI: 10.1111/micc.12100
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Effects of Human Monocytes and their Subsets on New Vessel Formation

Abstract: Our findings suggest additive and differential effects of monocyte subsets during neovascularization processes, possibly due to an altered secretion of angiogenic factors and their paracrine capacity to stimulate new vessel formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Mo are a heterogeneous cell population and it has been reported that Mo subsets possess distinct cell surface markers and functional characteristics relevant to their contribution to angiogenesis . The identification of different angiogenic properties of Mo prompted several investigators to perform studies to delineate the functional significance of each subset.…”
Section: Discussionmentioning
confidence: 99%
“…Mo are a heterogeneous cell population and it has been reported that Mo subsets possess distinct cell surface markers and functional characteristics relevant to their contribution to angiogenesis . The identification of different angiogenic properties of Mo prompted several investigators to perform studies to delineate the functional significance of each subset.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of inflammatory cells in hypoxic areas is a hallmark to tissue ischemia (Silvestre et al, 2008). Monocytes have been shown to promote angiogenesis by releasing angiogenic growth factors, cytokines, and metalloproteinases (Czepluch et al, 2014;Jaipersad et al, 2014). Interaction between monocytes and ECs results in crossmodulation of several biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…These cells perform various functions after MI, including removing damaged extracellular matrix and dying cardiac cells, releasing inflammatory mediators, and promote angiogenesis by releasing growth factors, cytokines and metalloproteinases [103,104]. Interestingly, macrophages have been observed to be able to carve out tunnels in the extracellular matrix mediating angiogenesis [105].…”
Section: The Role Of Apelin In Monocytes/macrophagesmentioning
confidence: 97%